Perbandingan Sosial dan Iri Hati (Envy) Pada Mahasiswa: Analisi Blibiometrik - Aufa Abdillah; Sri Lestari; Nisa Rahmah Nur Anganti; Taufik Taufik (Universitas Pahlawan Tuanku Tambusai, 2025)
Envy is a complex social emotion that frequently arises in interpersonal interactions, particularly through social comparison. Among college students, this emotion is further intensified by competitive academic environments and the influence of social media, which often serve as benchmarks for success and achievement. When not properly managed, envy can negatively impact students' mental health, especially in today’s digital era. This study aims to examine the trends and research patterns related to envy among college students through a bibliometric analysis approach. The analysis was conducted using VOSviewer software on 255 scientific articles indexed in the Scopus database from 1963 to 2025. Articles were selected based on three criteria: written in English, published in article format, and containing the keyword